Biochemical Alterations of Weeds in Response to Stress Caused by Herbicides and Total Plant Submersion - MARCHEZAN,M.G. (2017)
ABSTRACT: The maximum biological efficiency of a herbicide is performed when the plants are in favorable condition to absorb and metabolize it. Stress situations, such as total submersion, cause stress in plants, reducing weed control efficiency and crop yield. The objective of this study was to verify whether different soil water content and herbicide treatments alter the components of the secondary metabolism and cause cellular damage in weed species Two experiments were conducted (I and II) in a completely randomized experimental design with a factorial scheme (2 x 2 x 4 and 2 x 5, respectively) and three replicates. The first experiment was conducted with two species (Leersia hexandra and Luziola peruviana), which were submitted to four herbicide treatments and soil moisture levels (field capacity and total submersion). Experiment II was performed with cockspur grass plants submitted to five herbicide treatments and the same soil moisture levels from experiment I. Leaf samples were collected for laboratory analyses seven days after establishing the soil moisture levels. Assessmentes were made for the levels of chlorophyll and carotenoids, activity of antioxidant enzymes, as well as levels of hydrogen peroxide and cellular damage. The results showed that all plant species studied showed higher oxidative stress under field capacity than under submersion. L.hexandra shows greater oxidative stress than L. peruviana regardless of the treatment applied: water regime or herbicide. Furthermore, the associations of glyphosate + clomazone and glyphosate + mixture of imazapyr + imazapic caused greater oxidative stress in L.hexandra and L.peruviana than glyphosate alone. All herbicides caused lipid peroxidation, reduced enzyme activity decreased concentrations of total chlorophyll, chlorophyll a and carotenoids on cockspur grass.